Entrepreneurial Behavior and Innovative Behavior: A Conceptual Clarification - Amir, Muhammad Taufiq (The Asian Journal of Technology Management (AJTM), 2015)
Abstract. This paper represents one effort to systematize the use of terminology of entrepreneurial behavior and innovative behavior and to clarify how they relate each other. A clearly stated set of relationship and dynamics on these two concepts is necessary for scientific understanding, explanation and prediction. An agreed-upon relationship between entrepreneurial behavior and innovative behavior makes it easier for investigators to build on each otherâ€™s work, and for practitioners to decide whether research finding are applicable to them. Author first reviews some of the existing definitions on entrepreneurial behavior and innovative behavior and illustrates how they are mutually explaining and overlapping. Various terms used to describe the phenomena of interest are clarified. Endorsing, refining, and shepherding entrepreneurial opportunities are more related to idea generation phase of innovative behavior. While the other behaviors, identifying, acquiring and deploying resources needed to pursue entrepreneurial opportunities are more related to idea implementation phase of innovative behavior. Using the theory of socio-cognitive approach, pattern recognition and regulatory focus, the study details the discussion and concludes the overlap between entrepreneurial behavior and the innovative behavior. Keywords: Corporate entrepreneurship, innovation, innovative behavior; entrepreneurial behavior, socio-cognitive perspectiveÂ